The impact of structural changes on the actuation of polypyrroles - Melling, Daniel (Cranfield University, 2012)
A new non-contact method for characterizing the time-dependent mechanical performance of electro-active polymer films has been developed and is described in detail. We first illustrate our new measuring technique by investigating the impact of film thickness on the actuation performance of polypyrrole. Our method is simple to perform and serves as a valuable tool for studying the long term stability and operational failure of the films, the effects of synthesis conditions and for the optimization of actuator performance. We have used our technique to investigate the impact that structural changes, such as crosslinking, have on the actuation of polypyrroles. An understanding of this relationship is necessary if forms of polypyrrole are to be produced that are capable of greater movement, operating speeds, in service lifetimes and force generation. In order to do this we have developed a logical synthetic strategy (blocking approach) which allows us to change the degree of crosslinking in electro-synthesised polypyrrole. Using our blocking approach we have been able to show the impact that structural changes make on the actuation performance of polypyrroles. We have shown that it is possible to monitor crosslinking and branching changes in polypyrroles indirectly using the irreversible expansion of these films. Our measurements are a form of “dynamic swelling study” and are analogous with solvent swelling studies used in the polymer industry for monitoring cross-linking changes. The irreversible expansion of polypyrrole films has been used to investigate the effects that polymerization potential has upon the levels of cross-linking and branching. We go on to identify the optimal conditions for producing the maximum expansion, strain and strain rate for PPy(DBS). In addition, we have used instrumented indentation as a secondary method for monitoring crosslinking changes. This has provided information that is consistent with those revealed by changes in the irreversible expansion of the polymer. Finally we present an in-depth theoretical discussion of how elemental analysis could be used as a more direct way to quantitatively determine the levels of crosslinking within polypyrroles. This work represents the first study of its kind aimed at understanding the impact that crosslinking and branching has upon the actuation performance of polypyrroles. As a result we are closer to being able to synthesize polypyrroles with improved actuator properties such as greater strains and strain rates.